Solution of x^2 -nx-1=0 by Continued Fraction Method and Comparison of the Solution by Newton Raphson Method - A. Gnanam; S. Krithika (International Journal of Mathematics And its Applications, 2018)
In this paper we find the solution of the quadratic equation x^2 -nx-1 =0 using Continued Fraction method and identify the convergence of the solutions with other numerical methods such as Bisection method, False Position method, Iteration method and Newton Raphson method.